Biological production and recovery of 2, 3-butanediol using arabinose from sugar beet pulp by Enterobacter ludwigii. (May 2022) - Narisetty, Vivek; Narisetty, Sudheera; Jacob, Samuel; Kumar, Deepak; Leeke, Gary A.; Chandel, Anuj Kumar; Singh, Vijai; Srivastava, Vimal Chandra; Kumar, Vinod
Abstract: Sugar beet pulp (SBP) is a major byproduct from the sugar industries and consists of >20% w/w arabinose. The current work evaluated the potential of Enterobacter ludwigii assimilating pure arabinose and arabinose rich hydrolysate from SBP pellets for 2, 3-butanediol (BDO) production. The hydrolysate was obtained through dilute acid pretreatment (DAP) with sulphuric acid. The process was optimized for acid and solid loading to obtain a hydrolysate free from furan derivatives. The effect of different levels of substrate (10–60 g/L) using pure arabinose was conducted in shake flask experiments, followed by co-fermentation with small amounts of glucose and SBP hydrolysate. After flask cultivations, BDO fermentations were carried-out in a bench-top bioreactor in batch and fed-batch modes using pure arabinose as well as SBP hydrolysate. The fed-batch culture led to BDO production of 42.9 and 35.5 g/L from pure arabinose and SBP hydrolysate with conversion yields of 0.31 and 0.29 g/g, respectively. Finally, BDO accumulated on pure arabinose and SBP hydrolysate were recovered using an aqueous two-phase extraction system. The recovery yield of BDO accumulated on arabinose and hydrolysate was ∼97%. The work demonstrated the feasibility of using SBP as a suitable feedstock for manufacturing BDO. Graphical abstract: Image 1